Alexander von Humboldts Beurteilung der Solequellen in Slonsk (Słońsk) an der Weichsel im Jahr 1794, seine Vorschläge und wie es vor Ort weiterging - Hülsenberg, Dagmar; Juros , Józef Tomasz (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2025)
In 1794, on behalf of the Minister of State Baron von Heinitz, the Chief Inspector of Mines (Oberbergmeister) Alexander von Humboldt assessed the brine deposits in Slonsk on the Vistula for their mining potential. He assessed the conditions for the construction of a salt works and made suggestions on how to proceed. On this basis, the Prussian mining officials Friedrich Küster in 1798 and Alexander von Mielęcki in 1806 carried out drilling tests. The position of the boreholes could be confirmed by maps in Polish archives. The arrival of Napoleon’s army in the fall of 1806 interrupted the work on site. It was not until 1824 that the Polish entrepreneur Konstanty Leon Wolicki signed two contracts for the construction of a salt works. With the discovery of a copy of Humboldt’s report in 2015, his importance for the construction of a salt works and brine baths in Ciechocinek became apparent.